Residual methane emissions in grazing lactating dairy cows - Starsmore K; Lahart B; Villalobos-Lopez N; Egan M; Herron J; Burke JB; Shalloo L (Taylor and Francis Group, 2023)
Residual methane emission (RME) is a trait that has previously been identified as being independent of animal production traits. The objective of this study was to investigate the effect of ranking grazing dairy cows by RME on animal productivity and enteric methane (CH4) emissions. Milk production, dry matter intake (DMI), liveweight (LWT) and CH4 were recorded on grazing late lactation dairy cows at Teagasc Moorepark, Ireland. The dairy cows were producing 352 g CH4/day, while consuming 16.6 kg DM. The mean methane yield was 20.79 g CH4/kg DMI. Residual methane emission was calculated as the difference between measured CH4 yield and New Zealand emission factor (21.6 g CH4/kg DMI). These dairy cows were ranked based on their RME and classified into groups. The low RME group produced 15% less CH4 than the high RME group while maintaining milk production and feed conversion efficiency. The low RME group had lower methane yield, and methane intensity. There are no significant phenotypic correlations between RME and animal production traits such as energy corrected milk yield, or LWT. These results indicate that RME has the ability to select and rank low emitting grazing dairy cows while being independent from animal productivity traits.
Keywords: Enteric methane emissions; grazing dairy cattle; lactating dairy cow; pasture based; residual enteric methane emissions